At Lunch with a Killer: The Effect of Weaver Ants on Host-Parasitoid Interactions on Mango. - Valentina Migani; Sunday Ekesi; Katharina Merkel; Thomas Hoffmeister (PLoS ONE)
Predator-prey interactions can affect the behaviour of the species involved, with consequences for population distribution and competitive interactions. Under predation pressure, potential prey may adopt evasive strategies. These responses can be costly and could impact population growth. As some prey species may be more affected than others, predation pressure could also alter the dynamics among species within communities. In field cages and small observation cages, we studied the interactions between a generalist predator, the African weaver ant, Oecophylla longinoda, two species of fruit flies that are primary pests of mango fruits, Ceratitis cosyra and Bactrocera dorsalis, and their two exotic parasitoids, Fopius arisanus and Diachasmimorpha longicaudata. In all experiments, either a single individual (observation cage experiments) or groups of individuals (field cage experiments) of a single species were exposed to foraging in the presence or absence of weaver ants. Weaver ant presence reduced the number of eggs laid by 75 and 50 percent in B. dorsalis and C. cosyra respectively. Similarly, parasitoid reproductive success was negatively affected by ant presence, with success of parasitism reduced by around 50 percent for both F. arisanus and D. longicaudata. The negative effect of weaver ants on both flies and parasitoids was mainly due to indirect predation effects. Encounters with weaver ant workers increased the leaving tendency in flies and parasitoids, thus reduced the time spent foraging on mango fruits. Parasitoids were impacted more strongly than fruit flies. We discuss how weaver ant predation pressure may affect the population dynamics of the fruit flies, and, in turn, how the alteration of host dynamics could impact parasitoid foraging behaviour and success.